Sexual intimacy in couples is associated with longer telomere length. (July 2017) - Cabeza de Baca, Tomás; Epel, Elissa S.; Robles, Theodore F.; Coccia, Michael; Gilbert, Amanda; Puterman, Eli; Prather, Aric A.
Highlights: High-quality relationships are beneficial for physical and mental health. Frequency of sex has also been linked to greater mental and physical health. Sexual intimacy was associated with longer telomere length in whole blood and PBMCs. Sexual intimacy was not associated with granulocyte telomere length and telomerase. Abstract: High-quality relationships have been shown to be beneficial for physical and mental health. This study examined overall relationship satisfaction and perceived stress as well as daily reports of partner support, partner conflict, and physical intimacy obtained over the course of one week in a sample of 129 high and low stress mothers. Telomere length was examined in whole blood, as well as the two cell subpopulations: peripheral blood mononuclear cells (PBMCs) and granulocytes. Telomerase activity was measured in PBMCs. Analyses revealed no statistically significant associations of telomere length with current relationship satisfaction, daily support or conflict, or perceived stress. In contrast, women who reported any sexual intimacy during the course of the week had significantly longer telomeres measured in whole blood and PBMCs, but not in granulocytes. These relationships held covarying for age, body mass index, perceived stress, the relationship indices, and caregiver status. Sexual intimacy was not significantly related to PBMC telomerase activity. These data provide preliminary data that sexual intimacy is associated with longer telomere length. Future studies investigating these associations are warranted.